2008
DOI: 10.1044/1092-4388(2008/044)
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Fundamental Frequency and Sound Pressure Level Range on Breathing Patterns in Female Classical Singing

Abstract: Each singer maintained her characteristic kinematic pattern regardless of F0 or SPL range, although these did influence aspects of RC and AB behavior. Given the essential role of breathing in classical singing, further work is needed to understand how singers develop their highly individual respiratory strategies and the principles by which each singer's breathing strategy can be optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…(ellipses and italics in original). Two singers reported by Collyer et al (7) showed initial rib-cage paradoxing (Singers A and D), and the remaining three showed initial rib-cage contraction, with one showing initial abdominal paradoxing (Singer B). One would expect that this same directive would have different consequences for each singer, particularly for Singer B.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…(ellipses and italics in original). Two singers reported by Collyer et al (7) showed initial rib-cage paradoxing (Singers A and D), and the remaining three showed initial rib-cage contraction, with one showing initial abdominal paradoxing (Singer B). One would expect that this same directive would have different consequences for each singer, particularly for Singer B.…”
Section: Introductionmentioning
confidence: 93%
“…Each singer's lung volume estimation was normalized to her vital capacity range (%VC), and end expiratory level was calculated by averaging 20 consecutive cycles from the initial period of quiet breathing (7). The start and end of phonation in each phrase of the song were identified using the free-field microphone signal, and lung volume measurements at those points were recorded as lung volume at initiation (LVI) and lung volume at termination (LVT), respectively.…”
Section: Kinematic Directives and Breathing In Singing 103mentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that assessment of the influence of any directive on vocal quality must take into account how and to what extent CWK behavior has actually changed, especially given the wide differences in singers' kinematic strategies that have been observed. [21][22][23] It seems reasonable to assume that the singers studied by Swank 10 would have shown a similar interactive effect of habit and directive, but without CWK data the extent to which this might have affected the acoustical results cannot be determined.…”
Section: Introductionmentioning
confidence: 94%